Pilot study on tympanic temperature asymmetry and the lateralization of the epileptogenic zone - Filinto Ricardo Fernandes Vieira de Castro e Costa (2021)
Introduction: Lateralization of the epileptogenic zone remains challenging in some refractory epilepsy patients, and additional sources of information would be useful. There is evidence linking different states of autonomic activation with varying degrees of asymmetry in tympanic membrane temperature (ATMT), and epileptic seizures with hemodynamic changes in the internal carotid artery ipsilateral to the seizure onset in the peri-ictal period. We hypothesized that epileptic seizures could influence ATMT though these processes and that this asymmetry could correlate to the hemisphere of seizure onset. Methods: We recruited patients consecutively admitted to an epilepsy monitoring unit, where they were under video-EEG monitoring and measured their bilateral tympanic temperatures periodically. These measurements were compared to temperatures measured after any epileptic seizures (as soon as feasible, 5 minutes and one hour afterwards). Lateralization of seizures was determined by analysis of semiology and EEG records. Results: Patients who had seizures while admitted tended to have higher basal temperatures in their right ears, and five minutes after a seizure tympanic temperatures tended to be higher in the left ear, regardless of onset. Comparison of post-ictal temperature records from right and left-sided seizures suggested symmetrically opposite patterns of variation. Conclusion: Our results suggest that patients' basal ATMT might correlate with susceptibility to seizures, and also that the pattern of variation of this asymmetry between the immediate post-ictal and one hour post-ictal could help distinguish right from left hemisphere-onset seizures. A larger study sample will be necessary to draw more definitive conclusions.